The best slalom competitors - Kinematic analysis of tracks and velocities - Lesnik, B.; Zvan, M. (Kinesiology, 2007)
With the help of a kinematic analysis we tried to establish whether the competitors with a shorter line of skiing achieve higher velocities among the slalom gates. The first part of research found out that the competitors who had the shortest lines of skiing in the first analysed turn had, as a rule, the longest lines of skiing in the second turn and vice versa. The shortest line of skiing is therefore not a guarantee for the optimum entry into the next turn. This is confirmed by the negative and statistically insignificant degree of the correlation between the distances of the line of skiing of the competitors at the first and the second pole. On the basis of these findings, it could be claimed that under the present conditions, it is extremely difficult, maybe even impossible, to ski in such a way that the line of skiing would be very short in several successive turns. The second part of the research focused on the establishment of the correlation between the trajectories of the skis and the velocity of skiing of the chosen sample in the measured space (two slalom turns). The calculations of the correlations proved a statistically significant correlation between the average velocity of skiing and the average distance of the length of the line of skiing from the y-axis in the entire measured segment. It was established that the measured space was covered faster by the competitors whose line of skiing was shorter, which means more direct.